PRMT5 Prevents Cardiomyocyte Hypertrophy via Symmetric Dimethylating HoxA9 and Repressing HoxA9 Expression - Cai, Sidong; Liu, Rong; Wang, Panxia; Li, Jingyan; Xie, Tingting; Wang, Minghui; Cao, Yanjun; Li, Zhuoming; Liu, Peiqing (Frontiers in Pharmacology, 2020)
The present study reveals a link between protein arginine methyltransferase 5 (PRMT5) and Homebox A9 (HoxA9) in the regulation of cardiomyocyte hypertrophy. In cardiomyocyte hypertrophy induced by β-adrenergic receptor agonist isoprenaline (ISO), PRMT5 expression was decreased while HoxA9 was upregulated. Silencing of PRMT5 or inhibition of PRMT5 by its pharmacological inhibitor EPZ augmented the expressions of cardiomyocyte hypertrophic genes brain natriuretic peptide (BNP) and β-Myosin Heavy Chain (β-MHC), whereas overexpression of PRMT5 inhibited ISO-induced cardiomyocyte hypertrophy, suggesting that PRMT5 ameliorates cardiomyocyte hypertrophy. On the contrary, HoxA9 promoted cardiomyocyte hypertrophy, as implied by the gain-of-function and loss-of-function experiments. HoxA9 was involved in the regulation of PRMT5 in cardiomyocyte hypertrophy, since HoxA9 knockdown prevented si-RPMT5-induced cardiomyocyte hypertrophy, and HoxA9 expression impaired the anti-hypertrophic effect of PRMT5. Co-immunoprecipitation experiments revealed that there were physical interactions between PRMT5 and HoxA9. The symmetric dimethylation level of HoxA9 was decreased by ISO or EPZ treatment, suggesting that HoxA9 is methylated by PRMT5. Additionally, PRMT5 repressed the expression of HoxA9. Chromatin immunoprecipitation (ChIP) assay demonstrated that HoxA9 could bind to the promoter of BNP, and that this binding affinity was further enhanced by ISO or EPZ. In conclusion, this study suggests that PRMT5 symmetric dimethylates HoxA9 and represses HoxA9 expression, thus impairing its binding to BNP promoter and ultimately protecting against cardiomyocyte hypertrophy. These findings provide a novel insight of the mechanism underlying the cardiac protective effect of PRMT5, and suggest potential therapeutic strategies of PRMT5 activation or HoxA9 inhibition in treatment of cardiac hypertrophy.